MCTS exam 70-642 prep configuring Windows server 2008 networking infrastructure - Long, Mark.; Safari eBooks ([S.l.] : Virtual Training Co., 2005)
"Achieving the Microsoft Server Administrator MCITP certification is a great way to prove your knowledge, skill level and stand out to employers. Earning a Microsoft Server Administrator MCITP certification requires you to pass three exams: MS 70-640 Configuring Active Directory, MS 70-642 Configuring Network Infrastructure and MS 70-646 Windows Server 2008 Server Administrator. In this MCTS Exam 70-642 course, Microsoft Certified Trainer Mark Long covers the topics that will be on the exam. You will learn about TCP/IP Addressing and Subnetting, DHCP, IP Routing, DNS, File and Print Services and much more as Mark guides you through many of the steps so you can follow along. He also explains the technologies and points out a number of exam 'gotchas' to watch for, while directing you to more technical information for further study and preparation. Also included are work files, containing a TCP/IP Memorization Chart, Microsoft's WSUS Deployment Guide, a Step-By-Step Guide, as well as the WSUS 3.0 (SP2) installation file."--Resource description page.
Title from title screen (viewed Aug. 11, 2011).
Publication information from resource description page.
Keywords: Electronic data processing personnel -- Certification; Microsoft software -- Examinations -- Study guides; Microsoft Windows server; Electronic books